Decoding and reconstruction of digital video broadcast signals - Lim, Ricky Kim Poh (Nanyang Technological University, 2023)
The discussion of this project is to analyze available algorithms that simulate the Digital Video Broadcasting - second generation terrestrial (DVB-T2) signal transmission, propagation channel, and reception, with a focus on understanding the DVB-T2 signal decoding and reconstruction processes. The project will involve implementing a software-based simulation using MATLAB and analyzing the results to identify which algorithms are most effective in decoding and reconstructing with the DVB-T2, Common Simulation Platform (CSP).